Risk of social colours in an agamid lizard: implications for the evolution of dynamic signals. (15th May 2019) - Amdekar, Madhura S.; Thaker, Maria
Abstract : The forces of sexual and natural selection are typically invoked to explain variation in colour patterns of animals. Although the benefits of conspicuous colours for social signalling are well documented, evidence for their ecological cost, especially for dynamic colours, remains limited. We examined the riskiness of colour patterns of Psammophilus dorsalis, a species in which males express distinct colour combinations during social interactions. We first measured the conspicuousness of these colour patterns on different substrates based on the visual systems of conspecifics and predators (bird, snake, canid) and then quantified actual predation risk on these patterns using wax/polymer lizard models in the wild. The black and red male state exhibited during courtship was the most conspicuous to all visual systems, while the yellow and orange male aggression state and the brown female colour were least conspicuous. Models bearing the courtship colour pattern experienced the highest predator attacks, irrespective of the substrate they were placed on. Thus, social colours of males are not only conspicuous but also risky. Using physiological colours to shift in and out of conspicuous states may be an effective evolutionary solution to balance social signalling benefits with predation costs.